A Matter of Perspective?: The Emic and Etic Assessment of the Emergence of the First Free Evangelical Church in the Nineteenth Century in Germany - Heiser, Andreas (European journal of theology, 2024)
As a church historian, in this article I use the distinction between the "etic" and the "emic" perspective to analyse the historiography of the early Free Evangelical Churches in Germany. The first Free Evangelical Church was founded in Wuppertal in 1854 by Hermann Heinrich Grafe and its first historian was Heinrich Neviandt. Because church history examines the inner-worldly and at the same time other-worldly subject of ‘the Church’, I am arguing that the emic and the etic method and their respective possibilities should be differentiated and then used. The categories "etic" and "emic" do not determine right and wrong, real and unreal, true and untrue. Rather, their transfer from anthropology to historical research creates possibilities to describe the perspective from which scholars make their observations, as the work of Wolfgang Heinrichs shows. The two perspectives do not contradict one another and their distinction enables us to trace inner-worldly processes more clearly without resorting to God too quickly. Determining the driving forces behind history will remain the task of faith-based scholarship.